Pro Linux system administration : learn to build systems for your business using free and open source software / Dennis Matotek, James Turnbull, Peter Lieverdink - Matotek, Dennis
This book aims to ease the entry of businesses to the world of zero-cost software running on Linux. It takes a layered, component-based approach to open source business systems, while training system administrators as the builders of business infrastructu